Suspected seismo‐ionospheric coupling observed by satellite measurements and GPS TEC related to the M7.9 Wenchuan earthquake of 12 May 2008. Issue 12 (5th December 2014) - Ryu, K.; Parrot, M.; Kim, S. G.; Jeong, K. S.; Chae, J. S.; Pulinets, S.; Oyama, K.‐I.
Abstract: Anomalous changes in the ionospheric conditions related to the Wenchuan earthquake of 12 May 2008 are investigated using electron density ( N e ) from Detection of Electro‐Magnetic Emissions Transmitted from Earthquake Regions (DEMETER) and CHAMP satellites, electric field from DEMETER, and GPS‐total electron content (TEC) maps. The normalized N e from the DEMETER satellite reveal that the previously reported TEC increments before the earthquake can be considered as fragments of the gradual equatorial ionization anomaly (EIA) enhancements near the epicenter longitude that began approximately 1 month before the earthquake and reached its maximum with an exceptionally large strength index 8 days prior to the main shock. This feature is indirectly confirmed through the CHAMP N e and GPS TEC data. Following the EIA intensity peak, disturbances in the N e and O + density were observed in the nightside. Based on the concurrent electric field and N e changes, it is suggested that EIA intensification could be triggered by the E field disturbances over the epicenter. Key Points: Ionospheric disturbances before the Wenchuan earthquake are analyzed The TEC increase is revealed as the gradual EIA enhancements The nighttime data provide clues about geometry of seismo‐ionospheric coupling